“We try to give a good life to the children”-refugee parents and ECE professionals experiences of the early childhood education partnership in Norway - Lund, Hilde Hjertager (Frontiers in Education, 2024)
Children in Europe and Norway grow up in an increasingly culturally diverse society. As of 2022, 20 % of children in Norwegian Early Childhood Education (ECE) institutions have a minority background (Statistics Norway). It is essential for parents and ECE professionals to work together to ensure a good start for these children. The partnership between the ECE institutions and parents is a statutory right and duty, and parents should, on equal terms, participate and influence what happens in the ECE institutions (Ministry of Education and Research, 2017). However, research has shown a wide variation in how ECE professionals create partnerships with minority and refugee parents, and many find working with this group of parents challenging (Bergset, 2019;Lund, 2022b). This article explores the experiences of the interactions and encounters between refugee parents and ECE professionals in a Norwegian ECE setting. These interactions and encounters show tensions arising from differences in cultural norms and understandings among the refugee parents and the ECE professionals. The aim is to analyze the tensions in this partnership and provide insights into these encounters, negotiation processes and their experiences.The study is based on semi-structured interviews with twelve refugee parents, interviews with six pedagogical leaders, and one kindergarten manager. Additionally, fieldwork was conducted in one ECE institution to provide contextual depth. The data is analyzed thematically using an inductive research design. Through this analysis, three prominent themes emerged: 1) Barriers, 2) Norwegianness, and 3) Trust. The findings are discussed within the theoretical frameworks of cultural capital and power relations (Bourdieu